2020
DOI: 10.3906/elk-1906-66
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of railway switch point failures by artificial intelligence methods

Abstract: In recent years, railway transport has been preferred intensively in local and intercity freight and passenger transport. For this reason, it is of utmost importance that railway lines are operated in an uninterrupted and safe manner. In order to carry out continuous operation, all systems must continue to operate with maximum availability. In this study, data were collected from switch motors, which are the important equipment of railways, and the related equipment and these data were evaluated with sector ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The main embodiment of intelligence in high-speed railway was the integration of advanced technology methods represented by machine learning [13], [14] and high-speed railway networks. Intelligent failure diagnosis and prediction [5], [15], [16], condition monitoring and health management [17] were studied, such as failure intelligent diagnosis of rolling bearings [18], [19] or bogies [20], [21] of high-speed trains, switch failure prediction [22], [23], vehicle-body vibration prediction [24], as well as online condition monitoring of the pantograph slide plate [25]. It can be seen that machine learning methods have achieved remarkable results compared with the traditional methods.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The main embodiment of intelligence in high-speed railway was the integration of advanced technology methods represented by machine learning [13], [14] and high-speed railway networks. Intelligent failure diagnosis and prediction [5], [15], [16], condition monitoring and health management [17] were studied, such as failure intelligent diagnosis of rolling bearings [18], [19] or bogies [20], [21] of high-speed trains, switch failure prediction [22], [23], vehicle-body vibration prediction [24], as well as online condition monitoring of the pantograph slide plate [25]. It can be seen that machine learning methods have achieved remarkable results compared with the traditional methods.…”
Section: Related Workmentioning
confidence: 99%
“…Considering that train operation and maintenance were mutually exclusive, Liden et al [32], [33] presented a mixed integer programming model for Swedish Northern Main Line to solve the problems of integrated railway traffic and maintenance planning. The above research results showed that intelligent maintenance could reduce malfunction process time, save resources [22], and optimize the route planning of high-speed trains [34].…”
Section: Related Workmentioning
confidence: 99%
“…Along with the improvement of existing electric switches by replacing unreliable elements and electric motors, global companies are working to create new types [12]. Increasingly, turnouts are equipped with a modified drive system with microcontroller control.…”
Section: Introduction One Of the Main Directions Of Implementation Of The National Transport Strategy Ofmentioning
confidence: 99%
“…The ball-screw pair «screw-nut» converts the rotational movement of the screw ( 9) into the translational motion of the nuts (10). The screw is mounted on the support bearings (11) and connected to the motor shaft via a coupling (12). Nuts through vertical rods (13), hinges (14) and longitudinal rod (15) transmit forces to the sharpeners (7), which carry out their movement between the frame rail (8) [18].…”
Section: Introduction One Of the Main Directions Of Implementation Of The National Transport Strategy Ofmentioning
confidence: 99%
“…The test set samples are presented to the network once all weights have been determined. The network is considered to have been effectively trained if it responds correctly to the test set samples [9].…”
mentioning
confidence: 99%